A study on ductile fracture of coiled tubing based on cohesive zone model. (15th March 2019) - Zhao, Guanghui; Li, Ju; Zhang, Y.X.; Zhong, Jijia; Liang, Zheng; Xiao, Shihong
Graphical abstract: Highlights: Non-standard arc specimens of Coiled Tubing are tested to get its fracture feature. A method is established to determine the optimal parameters for Cohesive Zone Model. An optimal CZM is determined for modeling fracture process of CTs. Criterions for safety assessments of the cracked CT are proposed. Abstract: Aiming at the characteristics of small diameter and thin wall of coiled tubing (CT), arc specimens were cut from a length of CT longitudinally. Tensile tests were conducted to get elastic-plastic constitutive curve, and fracture tests were done to obtain relationships among loading force, load line displacement, crack tip opening displacement (CTOD) and crack propagation. Based on the results of the fracture tests, optimal cohesive parameters of Park-Paulino-Roesler (PPR) model for CT steel were determined by means of an inverse analysis based on the modifieded Levenberg-Marquardt optimization algorithm, and an effective cohesive zone model (CZM) was proposed for CT steel. By embedding the optimal CZM into the ABAQUS software via a user-defined subroutine UMAT, the ductile fracture of CT with a transverse surface crack was studied under two typical operating conditions: working in a wellbore and being wound back to a reel. Critical loading forces and critical crack sizes corresponding to crack initiation are determined, and methods of safety assessment for the cracked CT are given.